Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1212/wnl.0000000000010316
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-responsive and dopamine-resistant resting tremor in Parkinson disease

Abstract: Objective:We tested the hypothesis that there are two distinct phenotypes of Parkinson’s tremor, based on inter-individual differences in the response of resting tremor to dopaminergic medication. We also investigated whether this pattern is specific to tremor, by comparing inter-individual differences in the dopamine response of tremor to that of bradykinesia.Methods:In this exploratory study, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 48 publications
(72 reference statements)
4
58
0
4
Order By: Relevance
“…Not surprisingly, the magnitude of the levodopa responsiveness predicts the short‐term STN DBS responsiveness for bradykinesia and rigidity, which is concordant with the clinical observation and pathophysiological evidence in levodopa replacement therapy; 22,23 the severity of bradykinesia and rigidity are associated with the degree of nigrostriatal dopamine depletion 24,25 . However, for tremor, which is usually characterized by a combination of dopamine‐responsiveness and ‐resistance, 26 the magnitude of the short‐term STN DBS responsiveness was independent of the levodopa responsiveness. Indeed, STN DBS can effectively control levodopa‐responsive and ‐resistant tremors by modulating both dopaminergic and non‐dopaminergic neural circuits (e.g., the dentate‐rubrothalamic tract) 6 .…”
Section: Discussionsupporting
confidence: 70%
“…Not surprisingly, the magnitude of the levodopa responsiveness predicts the short‐term STN DBS responsiveness for bradykinesia and rigidity, which is concordant with the clinical observation and pathophysiological evidence in levodopa replacement therapy; 22,23 the severity of bradykinesia and rigidity are associated with the degree of nigrostriatal dopamine depletion 24,25 . However, for tremor, which is usually characterized by a combination of dopamine‐responsiveness and ‐resistance, 26 the magnitude of the short‐term STN DBS responsiveness was independent of the levodopa responsiveness. Indeed, STN DBS can effectively control levodopa‐responsive and ‐resistant tremors by modulating both dopaminergic and non‐dopaminergic neural circuits (e.g., the dentate‐rubrothalamic tract) 6 .…”
Section: Discussionsupporting
confidence: 70%
“…However, while these approaches seem to produce amelioration for most PD motor dysfunctions, they generate variable responsiveness for resting tremor (Helmich et al, 2012 ; Wu and Hallett, 2013 ; Connolly and Lang, 2014 ). The lack of dopamine-based therapies consistency with tremor could be explained by considering that based on the dopamine response, PD resting tremor can be divided into various partially overlapping phenotypes that may be associated with different pathophysiological mechanisms (Zach et al, 2020 ). These mechanisms might be produced by a cortical-subcortical network involving areas traditionally not directly related to PD.…”
Section: Introductionmentioning
confidence: 99%
“…One mainly due to a direct dopaminergic system deficiency and for which dopamine-based actions work. Others involving the dopaminergic system and other brain areas, for which dopamine-based treatments are less effective (Pasquini et al, 2018 ; Zach et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, PD resting tremor has a variable response to dopaminergic medication. In 30 of 76 tremor-dominant PD patients (39%), resting tremor did not respond at all to a levodopa challenge, while the remaining 46 patients (61%) showed an excellent response (64–81% reduction in tremor amplitude) [ 64 ]. A combined EMG-fMRI study showed that dopaminergic medication reduced tremor-related activity in the VIM and globus pallidus, but not in the cerebellum or M1 [ 65 ].…”
Section: Tremor In Parkinson’s Diseasementioning
confidence: 99%